Education On the Contents of My Plate to Mothers in an Effort to Prevent Stunting at Posyandu Melati 7 Kel. Bandar Selamat - Harahap, Reni Agustina; A'ini, Sharifah; Nst, Sopiah Widi Rahma (Universitas Malahayati, 2024)
ABSTRACT One of them is the problem of malnutrition, if food consumption is not fulfilled then the risk of nutritional problems arises, one of which decreases. Mother's nutritional knowledge influences diet and the quality of food provided. The higher the knowledge of nutrition, the more it affects the attitude and behavior of food consumption. One of the efforts to achieve a balanced diet is to use the